Structural phase transition study of FePt alloys using ab initio calculation - Imaizumi, Momotaro [UNESP]; Soufen, C. A. [UNESP]; Pintão, Carlos Alberto Fonzar [UNESP]; Varanda, L. C.; Jafeficci, M. [UNESP] (Elsevier B.V. Sa, 2009)
The FePt alloy undergoes the cubic to tetragonal lattice transformation in the ferromagnetic state. We calculated the electronic structure for both cubic and tetragonal structures using the FPLAPW method with APW + lo. Comparing the density of states of the cubic and tetragonal structures, it is expected that the lattice transformation is caused by the band Jahn-Teller effect. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Electronic structure; Cubic structure; Tetragonal structure; Density of states; Elastic constants